An Investigation on the Scientific Products: Iran, Turkey, and Greece - Kazerani, Maryam; Salahi Yekta, Ali; Nowzari, Sudabeh (Archives of Advances in Biosciences, 2010)
The present study seeks to investigate the scientific products among the three countries of Islamic Republic of Iran, Turkey, and Greece as they have entered the 3rd Millennium (during the years 2000-2008) upon the data obtained from ISI Web of Knowledge. In the past, these nations had possessed original, rich, and great civilizations; moreover, these countries had had (and still have) borders with each other so that Iran reflects itself as an Asian nation, Turkey as that of a Euro-Asian country, and Greece as a European nation. The findings show that at the turn of the 3rd Millennium (the year 2000); Turkey and Greece (with a little difference) had a higher level for the scientific products followed by Iran with a significant difference. After four years (in the year 2004), Turkey had taken the lead, followed by Greece and Iran. However, in the year 2008, Turkey had still had the lead in the generation of scientific products, while Iran had surpassed Greece.